Renewable updated History: A New Term for Framing Muslim Intellectual OutputYield - Al-Mekhlafi, Aref Ahmad Ismail (Journal of Arts, 2023)
The study intends to examine the historical thought writing methods, being among the most renewable up-to-date intellectual practices, spearheaded by competition among scholars and intellectuals in the pursuit of updated intellect and historical writing theories, in an attempt to find a comprehensive term for the intellectual productive output of Muslim scholars on the global thought output scale. The study is divided into two chapters. The first chapter dealt with new trends for reading and writing history. The second chapter discussed renewed updated history as a new term for framing Muslim intellectual productive output. The study concluded that ‘renewable updated history’ is a newly-created term closely relating Muslim intellectual contributions volume. It was also revealed that new history has not necessarily depicted everything the same way it was presented in history as a course detailing mankind’s biography since Divine creation. Historical documents are contingent upon writing; human mind is accuracy-driven, without which history would be nothing more than imaginary tales.